Significance of Photosynthetic Characters in the Evolution of Asian Gnetum (Gnetales) - Deng, Nan; Hou, Chen; Liu, Caixia; Li, Minghe; Bartish, Igor; Tian, Yuxin; Chen, Wei; Du, Changjian; Jiang, Zeping; Shi, Shengqing (Frontiers in Plant Science, 2019)
Gnetum is rich in bioactive compounds such as flavonoids and stilbenoids, which have been considered as important materials for traditional medicines and healthy food. Previous studies reveal that Gnetum has lower photosynthetic capacities than those of other seed plants. An explicit examination, however, is required since the investigated earlier samples were restricted to low numbers of species from narrow taxonomic and geographic ranges. Therefore, we conducted a study to investigate photosynthetic characteristics and composition of chloroplast genomes of five Chinese Gnetum species. We studied both Gnetum and co-occurring woody angiosperms in wild and also seedlings from different species of Gnetum in greenhouse. Our results showed that the five species of Chinese Gnetum had considerably lower levels of photosynthesis, including net photosynthetic rate, transpiration rate, intercellular CO2 concentration, stomatal conductance, than those of other seed plant representatives. These results are congruent with the results of the previous studies. Interrelated analyses revealed that low photosynthetic capacities may be an intrinsic property of Gnetum, indicating a unique evolutionary history and specific ecological adaptations in this ancient genus. In addition, through comparisons of plastid genomes among Gnetum and the representatives of other seed plants, we found that 17 coding genes were absent in this genus. This finding suggests that the lack of multiple functional genes in plastid genomes could lead to low photosynthetic rates we observed in different species of the genus. The present investigation of photosynthesis in both ecophysiological and genomic terms can provide a new perspective onevolutionary history of the Gnetales and tropical biomes in general. Our results can thus benefit the future research on breeding and cultivation of Gnetum and improve understanding of evolutionary ecology of tropical flora.